Seroprevalence of hepatitis E virus (HEV) and detection of HEV RNA with a transcription‐mediated amplification assay in blood donors from Catalonia (Spain). Issue 5 (18th November 2014) - Sauleda, Sílvia; Ong, Edgar; Bes, Marta; Janssen, Alanna; Cory, Robin; Babizki, Maria; Shin, Tim; Lindquist, Andre; Hoang, Anh; Vang, Lee; Piron, Maria; Casamitjana, Natàlia; et al.
<x xml:space="preserve">Abstract</x> Background Hepatitis E virus (HEV) is an emerging threat to the safety of blood transfusion. The aim of this study was to determine HEV immunoglobulin (Ig)G and RNA prevalence in Catalan blood donors. Study Design and Methods Nearly 10, 000 samples were collected from anonymized, unpaid donors at the Banc de Sang i Teixits (Barcelona, Spain) from June to December 2013. For the serology study, a subset of 1082 donations was tested in parallel for HEV IgG using Wantai and Mikrogen enzyme‐linked immunosorbent assay tests. Samples were tested individually (individual‐donation nucleic acid test [ID‐NAT]) for HEV RNA using the Procleix HEV assay (95% limit of detection 7.9 IU/mL). Procleix repeat‐reactive donations were confirmed by an in‐house real‐time polymerase chain reaction (PCR) test. Results The prevalences of IgG anti‐HEV in Catalan blood donors were 19.96% (Wantai assay) and 10.72% (Mikrogen assay). Screening of 9998 samples with the Procleix HEV assay yielded three real‐time PCR‐confirmed and IgM and IgG anti‐HEV–positive donations with viral loads of 250, 564, and 2755 IU/mL. The donation with highest viral load was genotype 3f. HEV RNA positivity rate was one per 3333 donations (0.03%; 95% confidence interval, 0.01%‐0.09%). Conclusion The Procleix HEV ID‐NAT screening system has provided evidence of HEV RNA presence in Catalan blood donors. Further data are needed to assess the impact of HEV infection in at‐risk patients to design the best strategy to increase blood safety.